Using Technology to Explore Social Networks and Mechanisms Underlying Peer Effects in Classrooms. - Guryan, Jonathan; Jacob, Brian; Klopfer, Eric; Groff, Jennifer (Developmental Psychology, 2008)
Peer interactions among children have long interested social scientists. Identifying causal peer effects is difficult, and a number of studies have used random assignment to produce evidence that peers affect each other's outcomes. This focus by sociologists and economists on whether peers affect each other has not been matched by direct evidence on how these effects operate. The authors argue that one reason for the small number of studies in sociology and economics on the mechanisms underlying peer effects is the difficulty of collecting data on microinteractiotis. They argue technology reduces data collection costs relative to direct observation and allows for realistic school activities with randomly assigned peers. The authors describe a novel strategy for collecting data on peer interactions and discuss how this approach might shed light on mechanisms underlying peer influence. The centerpiece of this strategy is the use of handheld computers by middle and high school students as part of interactive math and science lessons called the Discussion Game. The handhelds collect data on interactions between students and track how students' answers evolve as they interact with different peers. Reprinted by permission of the publisher.